2016
DOI: 10.1021/acs.chemrestox.5b00528
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant-Mediated Modulation of Protein Reactivity for 3,4-Dihydroxyphenylacetaldehyde, a Toxic Dopamine Metabolite

Abstract: 3,4-Dihydroxyphenylacetaldehyde (DOPAL) is an endogenously produced toxic aldehyde. It is a bifunctional electrophile implicated in the loss of dopaminergic cells concomitant with Parkinson’s disease and neurodegeneration. DOPAL is known to react with proteins and amino acids such as N-acetyl Lys; oxidation of the catechol moiety to the quinone of DOPAL increases this reactivity. Here we demonstrate the ability of the antioxidants N-acetylcysteine, glutathione, and ascorbic acid to mitigate the reactivity of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 47 publications
4
26
0
Order By: Relevance
“…Consistent with previous reports that a variety of antioxidants inhibit DOPAL reactivity with proteins (Rees et al, 2009;Follmer et al, 2015), treatment with NAC was remarkably effective in mitigating all the protein modifications exerted by DOPAL-quinonization, oligomerization, ubiquitination, and aggregation-as well as the inhibitory effect of DOPAL on LAAAD. The finding that NAC prevented DOPALinduced AS oligomerization replicates the report by Anderson et al (2016).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Consistent with previous reports that a variety of antioxidants inhibit DOPAL reactivity with proteins (Rees et al, 2009;Follmer et al, 2015), treatment with NAC was remarkably effective in mitigating all the protein modifications exerted by DOPAL-quinonization, oligomerization, ubiquitination, and aggregation-as well as the inhibitory effect of DOPAL on LAAAD. The finding that NAC prevented DOPALinduced AS oligomerization replicates the report by Anderson et al (2016).…”
Section: Discussionsupporting
confidence: 88%
“…To explore whether protein modifications exerted by DOPAL depend on its oxidation, we assessed effects of the antioxidant N-acetylcysteine (NAC). A variety of antioxidants interfere with DOPAL-induced oligomerization of AS (Follmer et al, 2015;Anderson et al, 2016). We chose NAC for the present experiments for several reasons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…156,163,164,177 In the few studies where DOPAL and dopamine have been compared directly in terms of oligomerizing AS, DOPAL has been found to be more potent. 156,163,171 We recently compared DOPAL and dopamine in terms of (1) AS oligomerization and quinonization in test tube experiments; (2) enhancing effects of Cu(II) 171,178 and mitigating effects of antioxidation with N-acetylcysteine (NAC) 134,156,179,180 ; and (3) quinonization of intracellular proteins in cultured cells. 134,156 We found that DOPAL is far more potent than dopamine in both oligomerizing and quinonizing AS.…”
Section: Interactions Of Dopamine Oxidation Products With α-Synucleinmentioning
confidence: 99%
“…137 Then work by Anderson et al used EPR to detect free radicals during DOPAL's interaction with N-acetyl lysine, an amino acid residue known to interact with DOPAL. 138 It was expected that the Schiffbase radical that is formed would give a splitting pattern that was comparable to the DOPAL radical, however these splitting patterns were absent. 138 Instead the splitting patterns were consistent with nitroxide free radicals derived from tricine, further supporting the evidence that tricine forms a stable radical.…”
Section: Resultsmentioning
confidence: 99%